Teacher's Strategy to Stimulate Cognitive Development of Early Children in the New Adaptation Period - Umi Hani; Naimah (Jurnal Pendidikan dan Pengajaran, 2022)
Changes in the implementation of learning by combining online and offline models during the new adaptation period require a new strategy for kindergarten institutions. The impact of change requires teachers to carry out effective and fun learning strategies in stimulating all aspects of early childhood development. This study was conducted to analyse the strategies that have been carried out by kindergarten teachers to stimulate the cognitive development of early childhood in the new adaptation period. This type of research uses a qualitative descriptive method with a case study approach. Sources of data in the form of documents (learning, photos, and videos) and credible sources. Qualitative data was collected through observation, documentation and in-depth interviews. The analysis was carried out inductively, continuously until the final findings of meaningful research were found. The results showed that the teacher's strategy stimulated early childhood cognitive development by; 1) presenting interesting themes and activities that are packaged in the form of stories (one of which is child adventure), 2) using a scientific approach and playing, involving family members, prioritizing learning resources for school and local wisdom based on projects at home, 3) using procedures and effective methods, 4) the application of norms for the success of children's achievements through process and outcome. The conclusion shows that the teacher's strategy in stimulating cognitive development is by preparing a clear plan of learning objectives and activity programs, implementing adaptive, effective and collaborative learning, normative evaluation and counselling guidance services.